CLASSIFICATION OF COGNITIVE LINGUISTIC PHENOMENA OF FRUIT TERMINOLOGY IN ENGLISH - Kenjayeva Barchinoy (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Cognitive linguistics studies the relationship between language, thought, and conceptualization. Fruit names in English are not only lexical items but also cognitive concepts formed by human perception, cultural connections, and linguistic conventions. Cognitive linguistics also aims to study the regular names of fruit names in English, as well as their relationships with other terms and their general structures. This article examines how the terminology of fruit names in English reflects various cognitive linguistic phenomena, including metonymy, categorization, metaphor, and conceptual blending.